Analisis Penanggulangan Kemiskinan melalui metode Sharing Profit pada Pengelolaan wisata “Pulau Ular” di Desa Pai Kecamata Wera Kabupaten Bima - Firdaus, Firdaus; Tasrif, Tasrif; Mulyawan, Wawan (Universitas Gajah Putih, 2022)
Tourism has an influence on economic growth through several channels (Brida et al, 2010). First, the tourism sector as a foreign exchange earner to obtain capital goods used in the production process (McKinnon, 1964). Second, tourism development stimulates investment in infrastructure (Sakai, 2006). Third, the development of the tourism sector encourages the development of other economic sectors through direct, indirect, and induced effects (Spurr, 2006). Fourth, tourism contributes to increasing job opportunities and increasing income (Lee & Chang, 2008). Fifth, tourism causes positive economies of scale (Weng & Wang, 2004). Tourism is also an important factor in the dissemination of technical knowledge, encouraging research and development, and the accumulation of human capital (Blake et al, 2006). The purpose of this study is to describe the process of Poverty Reduction through the Profit Sharing method in the management of